16-Channel micro magnetic flux sensor array for IGBT current distribution measurement. Issue 9 (August 2015) - Tomonaga, H.; Tsukuda, M.; Okoda, S.; Noda, R.; Tashiro, K.; Omura, I.
Abstract: Current crowding of IGBT and power diode in a chip or among chips is a barrier to the realization of highly-reliable power module and power electronics system. Current crowding occurs because of the parasitic inductance, difference of chip characteristics or temperature imbalance among chips. Although current crowding among IGBT or power diode chips has been analysed on numerical simulations, no sensor with sufficiently high special resolution and fast measurement time has yet been demonstrated. Therefore, the author developed and demonstrated 16-channel flat sensitivity sensor array for IGBT current distribution measurement. The sensor array consists of tiny-scale film sensors with analog amps and shield case against noise. The array and digital calibration method will be applied for reliability analysis, designing and screening of IGBT modules. Highlights: Current crowding of IGBT and power diode in a chip or among chips is a barrier to the realization of highly-reliable power module. The author developed and demonstrated 16-channel flat sensitivity sensor array for IGBT current distribution measurement. The sensor array consists of tiny-scale film sensors with analog amps and shield case against noise.